The Implication of Free Practice in Duolingo English Test on Students’ Speaking Skill and Their Experience For Iisma Program - Reyndi Reasklint (Fakultas Keguruan Dan Ilmu Pendidikan, 2024)
Speaking is a productive oral skill that consists of producing systematic verbal utterances to convey meaning (Bailey, 2007). Related with speaking skill, it is described as productive skill (how to produce speech) or oral skill (clarity to transmit ideas from you to other people) in speaking (Bailey, 2007). Speaking skill can also be honed with mobile learning which is the full use of mobile phone technology in learning, and users use mobile technology as they learn (Setyantoko, 2016). One popular mobile learning technology that helps students in honing speaking skill is Free Practice in DET (Duolingo English Test), especially for those who want to join international programs such as IISMA. Then, this research was intended to examine the experience and Implications of the Free Practice in Duolingo English Test on Students' Speaking Skill at university during preparation for the actual Duolingo English Test for IISMA program.
Repo 14 April 2026_ Rudy K
Keywords: The Implication of Free Practice